The Wednesday wars - Schmidt, Gary D. (Sandpiper Books, 2007)
During the 1967 school year, on Wednesday afternoons when all his classmates go to either Catechism or Hebrew school, seventh-grader Holling Hoodhood stays in Mrs. Baker's classroom where they read the plays of William Shakespeare and Holling learns much of value about the world he lives in.